Development of Souvenir Products with the Application of Brile's Font - I. Bratisheva, Yu.; Yu. Mamedova, I. (International Journal of Engineering and Technology, 2018)
The modern world is impulsive and impetuous. Sometimes people simply do not think about people with disabilities, hence the social needs of these people are not perceived. However, there are a lot of such individuals–they are born with illnesses, or acquired during life –these individuals are people with hearing loss, visually impaired, with disorders of the musculoskeletal system, and etc. This work developed a statuette, symbolizing 15 years of marriage for the visually impaired couples.